Neuroimaging findings in newborns with congenital heart disease prior to surgery: an observational study - Kelly, Christopher J; Arulkumaran, Sophie; Tristão Pereira, Catarina; Cordero-Grande, Lucilio; Hughes, Emer J; Teixeira, Rui Pedro A G; Steinweg, Johannes K; Victor, Suresh; Pushparajah, Kuberan; Hajnal, Joseph V; Simpson, John; Edwards, A David; et al. (Archives of disease in childhood, 2019)
ObjectivesNeurodevelopmental impairment has become the most important comorbidity in infants with congenital heart disease (CHD). We aimed to (1) investigate the burden of brain lesions in infants with CHD prior to surgery and (2) explore clinical factors associated with injury.Study designProspective observational study.SettingSingle centre UK tertiary neonatal intensive care unit.Patients70 newborn infants with critical or serious CHD underwent brain MRI prior to surgery.Main outcome measuresPrevalence of cerebral injury including arterial ischaemic strokes (AIS), white matter injury (WMI) and intracranial haemorrhage.ResultsBrain lesions were observed in 39% of subjects (95% CI 28% to 50%). WMI was identified in 33% (95% CI 23% to 45%), subdural haemorrhage without mass effect in 33% (95% CI 23% to 45%), cerebellar haemorrhage in 9% (95% CI 4% to 18%) and AIS in 4% (95% CI 1.5% to 12%). WMI was distributed widely throughout the brain, particularly involving the frontal white matter, optic radiations and corona radiata. WMI exhibited restricted diffusion in 48% of cases. AIS was only observed in infants with transposition of the great arteries (TGA) who had previously undergone balloon atrial septostomy (BAS). AIS was identified in 23% (95% CI 8% to 50%) of infants with TGA who underwent BAS, compared with 0% (95% CI 0% to 20%) who did not.ConclusionsCerebral injury in newborns with CHD prior to surgery is common.